Two New Spider Species of the Genus Draconarius (Araneae, Amaurobiidae, Coelotinae) from Pakistan - Ovtchinnikov, S.V.; Inayatullah, M. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
Draconarius pakistanicus Ovtchinnikov, sp. n. and D. naranensis Ovtchinnikov, sp. n. from Pakistan are described. The typical loci for Coelotes bifidus Caporiacco, 1935 and C. stylifer Caporiacco, 1935 are determined. Three species of the family Amaurobiidae (subfamily Coelotinae) are known now from Pakistan: C. stylifer Caporiacco, 1935 was actually described from India, not from Pakistan.